2010
DOI: 10.1371/journal.pone.0009051
|View full text |Cite
|
Sign up to set email alerts
|

Role of QuantiFERON-TB Gold, Interferon Gamma Inducible Protein-10 and Tuberculin Skin Test in Active Tuberculosis Diagnosis

Abstract: BackgroundThe measurement of Interferon gamma or Interferon gamma inducible protein (IP)-10 in antigen stimulated blood samples is suggested as an alternative method for latent tuberculosis (TB) diagnosis. Nonetheless, their role in active TB diagnosis, particularly in TB endemic settings is yet to be defined. In this study, the sensitivities and specificities of Interferon gamma release assay (IGRA), IP-10 assay and tuberculin skin test (TST) in detecting active TB cases were assessed in human immunodeficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 38 publications
(41 reference statements)
6
60
6
Order By: Relevance
“…Combining the tests significantly increased sensitivity to 96% in HIV-negative and 88% in HIV-positive patients (table 1). We and others have found a similar improvement in sensitivity among patients from low-endemic setting without a compromise in specificity [8,9]. Thus, combining tests appears to be a feasible way to improve performance of the antigen-specific assays.…”
Section: To the Editorssupporting
confidence: 57%
“…Combining the tests significantly increased sensitivity to 96% in HIV-negative and 88% in HIV-positive patients (table 1). We and others have found a similar improvement in sensitivity among patients from low-endemic setting without a compromise in specificity [8,9]. Thus, combining tests appears to be a feasible way to improve performance of the antigen-specific assays.…”
Section: To the Editorssupporting
confidence: 57%
“…For the T-SPOT.TB assay, the sensitivity was between 79 and 95% and the specificity was between 64% and 100% for active TB in HIV-infected patients (74). The sensitivity of the QFT-GIT test for culture-confirmed pulmonary TB in HIV-infected patients ranged from 65% to 91% in previously reported studies, and the likelihood of indeterminate results increased with lower CD4 counts (1,9,74,158,177,242,254). Aabye et al found that 22% of HIV-infected patients with culture-confirmed pulmonary TB had indeterminate results with the QFT-GIT test, and patients with CD4 counts below 300 cells/l were nearly 3 times as likely to have indeterminate results as patients with CD4 counts above 300 cells/l (1).…”
Section: Ifn-␥ Release Assays For Hiv-infected Patientsmentioning
confidence: 92%
“…The diagnostic potential of IP-10 (125) also has been evaluated, with mixed results (54,149,167). Since secretion of IP-10 is less affected than that of IFN-␥ by immunosuppression (55) and is age independent (85), IP-10 has been proposed as an adjunct marker of LTBI diagnosis in pediatric and HIV-coinfected populations (85,124).…”
Section: Cellular Immune Responses and Infection Statementioning
confidence: 99%